PARAMETRIC DESIGN AND BIM FOR ADAPTIVE RAPID DEPLOYMENT SHELTERS CONSIDERING MULTI-CRITERIA OPTIMIZATION - Hrechka, Uliana Mykhailivna (Theory and practice of design, 2025)
The relevance of this study is determined by the growing need for rapid infrastructure recovery, the deployment of mobile shelters, and the development of resilient housing solutions under emergency conditions. In the post-war reconstruction phase of Ukraine, the implementation of digital technologies in the construction sector has gained particular importance, as it enhances adaptability, energy efficiency, and resource optimization. Contemporary challenges demand a transition from static architectural design to parametrically controlled and analytically justified models capable of ensuring integrated lifecycle management of shelters. The aim of this article is to develop a scientifically grounded concept for the use of parametric design and Building Information Modeling (BIM) technologies to create adaptive rapid deployment shelters that consider the multi-criteria optimization of structural, energy, and functional parameters. The research methodology is based on a systems approach that integrates methods of parametric modeling, multi-criteria optimization, BIM, and building lifecycle management. The study employs the principles of the Common Data Environment (CDE) and analytical comparison of design alternatives based on energy efficiency, mobility, cost, and environmental sustainability. The synthesis is based on the analysis of international and Ukrainian pilot projects, including RE:Ukraine Housing. The results show that integrating parametric design with BIM technologies provides an effective synergy between geometric modeling, techno-economic analysis, and operational analytics. It has been demonstrated that such integration allows the development of digital shelter models capable of automatically adapting to climatic, logistical, and resource constraints. The main implementation challenges identified include technical incompatibility of software environments, the regulatory uncertainty regarding the legal status of digital models, and the shortage of qualified specialists. The scientific novelty lies in developing a comprehensive concept for digital lifecycle management of adaptive shelters based on the integration of parametric modeling, multi-criteria optimization, and the BIM approach. For the first time, the structure of an integrated CDE for mobile structures has been substantiated, enabling interoperability among architectural, engineering, logistical, and analytical subsystems. The practical significance of the research lies in the possibility of using the obtained results to establish an effective digital management system for the design, deployment, and operation of shelters. The proposed solutions can be integrated into national reconstruction programs, digital construction standards compliant with ISO 19650, as well as international humanitarian initiatives for modular housing.